Pasts at play : Childhood encounters with history in British culture, 1750-1914 - Gribling, Barbara; Davies, Rachel Bryant (Book collections on Project MUSE., 2020)
Pasts at play showcases a range of approaches to children's literature and culture, from disciplines including Classics, English Literature, and History. The ten essays integrate visual and material culture into historical practice to analyse how nineteenth-century children interacted playfully with the past to generate moral lessons.